1998
DOI: 10.1074/jbc.273.30.19235
|View full text |Cite
|
Sign up to set email alerts
|

ZmcPKC70, a Protein Kinase C-type Enzyme from Maize

Abstract: The crucial enzyme in diacylglycerol-mediated signaling is protein kinase C (PKC). In this paper we provide evidence for the existence and role of PKC in maize. A protein of an apparent molecular mass of 70 kDa was purified. The protein showed kinase activity that was stimulated by phosphatidylserine and oleyl acetyl glycerol (OAG) in the presence of Ca 2؉ . Phorbol 12-myristate 13-acetate (PMA) replaced the requirement of OAG. [ 3 H]PMA binding to the 70-kDa protein was competed by unlabeled PMA and OAG but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 71 publications
0
14
0
1
Order By: Relevance
“…Although PKC-like enzyme activity has been shown in plants (Subramaniam et al, 1997), its corresponding gene in the Arabidopsis genome has not been identified. However, diacyl glyceroldependent PKC homologous genes have been isolated from other plants, and showed to function in plant defense responses including production of defensive secondary metabolites (Chandok and Sopory, 1998;Subramaniam et al, 1997;Vasconsuelo et al, 2003Vasconsuelo et al, , 2004. In this work, the complete inhibition of lead-induced ROS production by the calmodulin inhibitor W7 (Figure 7) suggested the role of calmodulin in NADPH-oxidase-like enzyme activation.…”
Section: Discussionmentioning
confidence: 78%
“…Although PKC-like enzyme activity has been shown in plants (Subramaniam et al, 1997), its corresponding gene in the Arabidopsis genome has not been identified. However, diacyl glyceroldependent PKC homologous genes have been isolated from other plants, and showed to function in plant defense responses including production of defensive secondary metabolites (Chandok and Sopory, 1998;Subramaniam et al, 1997;Vasconsuelo et al, 2003Vasconsuelo et al, , 2004. In this work, the complete inhibition of lead-induced ROS production by the calmodulin inhibitor W7 (Figure 7) suggested the role of calmodulin in NADPH-oxidase-like enzyme activation.…”
Section: Discussionmentioning
confidence: 78%
“…The kinase activity of this enzyme was stimulated by calcium, PtdSer and oleyl-acetyl-glycerol or PMA. Moreover, it was shown that the labelled [ 3 H]PMA is able to bind to purified protein kinase [16]. A protein kinase resembling the mammalian PKC has been also partly purified from Brassica campestris seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Our data do not exclude the possibility of the presence in plants of a structural homolog of PKC. Recently a protein kinase of apparent molecular mass of 70 kDa was purified from etiolated leaves of maize [16]. The kinase activity of this enzyme was stimulated by calcium, PtdSer and oleyl-acetyl-glycerol or PMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…동물에서 DAG는 Ca 2+ 을 통하여 protein kinase C (PKC)의 활성을 촉진하여 신호 자극이 protein phosphorylation-dephosphorylation 반응으로 전환된다 [14]. 한편, 옥수수에서도 protein kinase C-type (ZmcPKC70) 이 확인되고, 이 효소는 phorbol 12-myristate 13-acetate (PMA)에 의해 조절되며, staurosporine (STA)에 의해 억제되 었다 [2]. Szczegielniak (Fig.…”
unclassified